Multi-instrument investigation of a mesospheric gravity wave event absorbed into background - Sivakandan, M.; Taori, A.; Sathishkumar, S.; Jayaraman, A. (My University, 2015)
We investigate a gravity wave event exhibiting dissipation noted in the mesospheric O(1S) airglow emission image measurements, over Gadanki (13.5°N, 79.2°E), on 16 March 2012 (during 16:20–16:45 UT). These gravity waves were found to propagate from south-west to north-east directions at ~65° azimuth in OH as well as in O(1S) images. These waves had horizontal wavelength ~21.5 km with apparent horizontal phase speed ~49 m s−1 and period ~7.3 min. These waves were noted to fizzle out in turbulent patches within 15 min. To identify the causative mechanism of this event, we analyze the background wind and temperature data using the medium-frequency radar wind from Tirunelveli (8.7°N, 77.8°E), ground-based Rayleigh lidar temperature data with improved capability over Gadanki, and spaceborne Sounding of the Atmosphere using Broadband Emission Radiometry/Thermosphere Ionosphere Mesosphere Energetics and Dynamics temperature data (20:30 UT) for a latitude-longitude grid of 3–23°N, 60–100°E. Our analysis reveals that convective instability was responsible for the observed event.
Keywords: Mesospheric gravity; Gravity waves